Residual Gauge Invariance in a Massive Lorentz-Violating Extension of QED - Marques, B. Alves; Scarpelli, A. P. Baêta; Felipe, J. C. C.; Brito, L. C. T. (Advances in High Energy Physics, 2022)
We reassess an alternative CPT-odd electrodynamics obtained from a Palatini-like procedure. Starting from a more general situation, we analyze the physical consistency of the model for different values of the parameter introduced in the mass tensor. We show that there is a residual gauge invariance in the model if the local transformation is taken to vary only in the direction of the Lorentz-breaking vector. This residual gauge invariance can be extended to all models whose only source of gauge symmetry breaking is such a mass term.